Caravanserai as a Tourism Destination: Case Study in Iran and Türkiye - Samsudin, Aina Zafirah; Sidik @ Mat Sidek, Roziah (Journal of Al-Tamaddun, 2025)
Caravanserais were constructed as rest stops and shelters, developed by the government free of charge for merchants, travellers, and pilgrims to rest before continuing their journeys. In addition to serving as stopovers, caravanserais were seen as potential tourism destinations that provided opportunities to explore their history and culture more closely. This study was conducted to examine caravanserais that became tourism destinations in Türkiye and Iran, and to identify the factors that formed significant links between caravanserais and tourism. The study adopted a qualitative research design using descriptive methods. Research topics and aspects were identified through literature review, research objectives, findings, and scope of discussion. Article sampling was carried out in two stages: first, by searching for articles using keywords such as “caravanserai,” “caravanserai and tourism,” and “UNESCO recognition”; second, by reviewing the reference lists at the end of the initially selected articles. Data analysis was conducted in stages, beginning with explicit content analysis followed by implicit content analysis. The findings showed that caravanserais gradually evolved into tourism destinations, linked to two main factors: the facilities provided, which attracted tourists, and UNESCO World Heritage recognition.